THE INFLUENCE OF INFLIXIMAB THERAPY ON BONE MINERAL DENSITY IN PATIENTS WITH ANKYLOSING SPONDYLITIS - T A Raskina; O A Pirogova (Остеопороз и остеопатии, 2013)
Introduction. There is evidence that patients with ankylosing spondylitis (AS) in the early stages of the disease have a significantly decreased bone mass. However, the prevalence of osteoporosis, and the mechanism of its development in the AS are poorly understood. The appearance of inhibitors of tumor necrosis factor alpha (TNF-α) significantly improved the prognosis and quality of life of patients with AS. The largest clinical experience has been gained in relation to infliximab (INF). Purpose. To assess the impact of IFN therapy on BMD of the femoral neck in patients with AS. Materials and Methods. We observed 65 male patients with a diagnosis of AS (according to the modified New York criteria 1984). In a deployed or late stage of the disease, with a high degree of activity — BASDAI > 4.0. All patients were divided into 2 groups: group 1 (n=25) — patients receiving combination therapy NSAIDs and IFN, group 2 (n=40) — patients with monotherapy at standard doses of NSAIDs (diclofenac 150 mg/ day, 200 mg of nimesulide/day meloxicam, 15 mg/day). IFN was administered a dose of 5 mg/kg of patient body weight: 1st day after 2 weeks and 6 weeks after the first injection, and after every 8 weeks. Follow-up for BMD was performed at 0 and 24 months. Results. We saw the BMD reduction at femoral neck in all patients with AS. During therapy with IFN BMD parameters showed a trend toward stabilization, which is probably due to a decrease in activity of the disease.